2019
DOI: 10.1002/hed.25989
|View full text |Cite
|
Sign up to set email alerts
|

Utility of negative‐pressure wound therapy for orocutaneous and pharyngocutaneous fistula following head and neck surgery

Abstract: Background: Because of the difficulty of airtight sealing and risk of salivary contamination, negative-pressure wound therapy (NPWT) has rarely been applied for postoperative fistula following head and neck surgery; thus, its utility remains unclear. Methods: We applied NPWT in 34 patients who developed orocutaneous and pharyngocutaneous fistula after head and neck surgery. Here we retrospectively analyzed the utility of NPWT for managing those fistulas. Results: Thirty-two patients (94.1%) underwent NPWT as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Another frequent indication for the use of NPWT in the head and neck are pharyngocutaneous fistulas post laryngectomy or pharyngolaryngectomy [8]. Different approaches have been used for the management of fistula tracts in the pharynx with the use of either conventional external foam dressing attached to a vacuum device or the use of intraluminal NPWT for the closure of the tract or the optimization of pharyngeal reconstruction [11,15]. Conventional daily dressing management is a cumbersome process involving a prolonged hospital stay and an additional financial burden on the healthcare system, with no convincing results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another frequent indication for the use of NPWT in the head and neck are pharyngocutaneous fistulas post laryngectomy or pharyngolaryngectomy [8]. Different approaches have been used for the management of fistula tracts in the pharynx with the use of either conventional external foam dressing attached to a vacuum device or the use of intraluminal NPWT for the closure of the tract or the optimization of pharyngeal reconstruction [11,15]. Conventional daily dressing management is a cumbersome process involving a prolonged hospital stay and an additional financial burden on the healthcare system, with no convincing results.…”
Section: Discussionmentioning
confidence: 99%
“…The undulating wound surfaces and movements of the neck pose problems of air leak and frequent dressing change with no effective outcome. Small maneuvers, such as the shallow insertion of foam dressing in the fistulous tract, the use of a tracheostomy tube with bulb inflation, a slight increase in negative pressure for large sized openings, bending or slightly turning the neck to the ipsilateral side, and the use of intraluminal foam dressings if the fistula is too large, seem to be successful [15,31]. Similarly, there is controversy regarding the placement of NPWT instead of synthetic or inert materials such as reconstruction titanium plates, synthetic vascular grafts, and mesh.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean time to fistula closure was 30.4 days, and did not differ with previously irradiated patients. 31 A systematic review by Lin et al also revealed success with NPWT. Although the exact method of NPWT varied, reported fistula closure rate ranged from 78 to 100% between studies.…”
Section: Negative Pressure Wound Therapymentioning
confidence: 99%